Antifungal edible coatings to reduce postharvest decay and preserve the quality of ‘Mollar de Elche’ pomegranates - Palou, Lluís; Alvarez, María Victoria; Taberner, Verónica; Pérez-Gago, María B. (2025)
Pomegranate exhibits important postharvest quality losses that limit its storage potential, caused mainly by weight loss, chilling injury, and fungal diseases. In this work, the effect of antifungal edible coatings (AECs) formulated with different biopolymers (citrus pectin (PEC), λ-carrageenan (CARG), and their combination PEC-CARG), beeswax (BW) as hydrophobic component, and 0.5% essential oils [EOs, cinnamon (CN) or lemongrass (LG)] as antifungal ingredients were evaluated to control weight loss and natural fungal decay of ‘Mollar de Elche’ pomegranates during storage at ambient temperatures (20°C). Results showed that PEC-based AECs were the most effective in reducing pomegranate decay caused by latent infections by Botrytis cinerea and wound infections by Penicillium spp. During 8 weeks of storage, with no significant differences between coatings formulated with CN or LG EOs. Furthermore, PEC-based coatings also reduced weight loss without causing visible phytotoxicity, while CARG-based coatings were slightly detrimental to the fruit rind. Afterwards, selected AECs were assayed to control natural decay and preserve fruit quality of pomegranates stored at 5°C for 12 weeks plus 1 week of shelf life at 20°C. PEC-based coatings were confirmed as an effective means to reduce weight loss and prevent fruit shriveling of cold-stored pomegranates without negatively affecting the fruit's physicochemical and sensory quality. However, no significant differences in latent and wound external decay were found between control and coated fruits after cold storage and shelf life. In conclusion, PEC-based coatings containing CN or LG EOs at 0.5% could be a promising treatment to extend the postharvest life of ‘Mollar de Elche’ pomegranates, although further studies are required to improve their antifungal effect during cold storage.